Catalyst-free tandem halogenation/semipinacol rearrangement of allyl alcohols with sodium halide in water. Issue 11 (1st May 2018) - Zeng, Zhixuan; Xun, Xudong; Huang, Liwu; Xu, Jiecheng; Zhu, Gongming; Li, Guofeng; Sun, Wangsheng; Hong, Liang; Wang, Rui
Abstract : A convenient procedure for the synthesis of β-haloketones via the tandem halogenation/semipinacol rearrangement of allyl alcohols with NaX. Abstract : An economical, convenient and eco-friendly procedure for the one-pot synthesis of β-haloketones with an α-quaternary carbon center via the tandem halogenation/semipinacol rearrangement of allyl alcohols with NaX (X = Cl, Br, I) in H2 O under open-air conditions has been demonstrated. The catalyst-free process affords various halogenated products in moderate to excellent yields (up to 98%). The features of this procedure include catalyst-free process, aqueous medium, low-cost sodium halide, open-air conditions, excellent yield and gram scalable preparation.